Modeling and controlling a robotized medical instrument - Caravaca-Mora, Oscar Mauricio (Instituto Tecnológico de Costa Rica, 2016)
During the last decade, Minimally Invasive Surgeries (MIS) have become a trend in the medical field, given the numerous benefits such as: reduced trauma, shorter recovery time and minimal postoperative complications. It has been promoted by the development of new technologies mainly in the field of robotics. Robotic technologies has emerged as a great option to create solutions that enhance the surgeon's perception and dexterity and allows access to often inaccessible human body places by keeping the smallest incision as possible. This document describes the modeling and control of a hand-held robotized medical instrument using stereo vision feedback, with the purpose of providing automatic assistance to the surgeon during the surgical procedure. The system modeling, simulation, experimental evaluation and results will be presented in this thesis document.
Proyecto de Graduación (Maestría en Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2016.
Keywords: Visión artificial; Robótica; Atención médica